2019
DOI: 10.1097/ruq.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Performance of B-Mode Ultrasonography and Shear Wave Elastography in Cervical Lymph Nodes

Abstract: The purpose of this study was to compare the diagnostic performance of B-mode ultrasonography (US) and shear wave elastography (SWE) for differentiating benign from malignant cervical lymph nodes (LNs). This study evaluated 130 cervical LNs in 127 patients. On conventional B-mode US, short-axis and long-axis diameters, long-to-short-axis ratio, cortical morphology, border, and presence of necrosis or calcification were evaluated. Maximum elasticity value (Emax) was collected for SWE. The area under the receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The eligible 10 articles with 590 patients (333 female and 257 male) were included in our study [13][14][15][16][17][18][19][20][21][22]. Seven of them were designed prospectively and 3 were retrospectively.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…The eligible 10 articles with 590 patients (333 female and 257 male) were included in our study [13][14][15][16][17][18][19][20][21][22]. Seven of them were designed prospectively and 3 were retrospectively.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The intrinsic curvature of the neck and the superficial location of cervical lymph nodes can cause inhomogeneous stress distribution in the field of observation, though the primary thyroid cancer would have advantages in SSI in terms of its hardness [14,22]. In addition, the older subgroups showed a trend of lower sensitivity but higher specificity for both A c c e p t e d A r t i c l e mean and max elastic moduli.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Desmots et al reported a similar finding in another study on 62 LNs ( 13 ). However, Kang et al reported the opposite finding in a study of 130 LNs ( 14 ). Biological heterogeneity in the samples from different studies could partially contribute to the observed differences, such as the cell type and histology of the studied LNs.…”
Section: Discussionmentioning
confidence: 91%
“…However, although most of these studies demonstrated the ability of SWE in differentiating malignant cervical LNs from benign ones as well as in even more challenging subgroups, a standard quantitative elasticity modulus metric and a recommended threshold have not been established, especially in terms of the quantitative metric used for measuring elasticity modulus and selected ROI. Furthermore, inconsistent performances of SWE were also reported ( 13 , 14 , 20 ). A few studies reported an improvement of diagnostic accuracy with SWE compared with conventional US ( 13 , 20 ), while another study failed to show that ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation